2017
DOI: 10.1016/j.ijheatmasstransfer.2017.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of force balance at vapour condensation on a cylindrical fin

Abstract: Abstract:Experimental investigation of vapour condensation on single cylindrical fin has been carried out under various gravity conditions: 1g0, 1.8g0 and 0.05g0. For the first time, a balance of forces acting on the condensate flow is analyzed. The fin surface is divided in seven areas, each one being characterized by the main force acting on the liquid motion: gravitational vs surfacetension pressure gradient. The magnitude of the areas does not depend on the gravity level. This confirms the correctness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Will it remain stable? Paper [14] gives an example of an unstable film in the low ∇p c area. In that paper authors experimentally investigated vapour condensation on a single cylindrical fin under various gravity conditions.…”
Section: Concept Of the Investigationmentioning
confidence: 99%
“…Will it remain stable? Paper [14] gives an example of an unstable film in the low ∇p c area. In that paper authors experimentally investigated vapour condensation on a single cylindrical fin under various gravity conditions.…”
Section: Concept Of the Investigationmentioning
confidence: 99%
“…Shigeki [75] conducted an experimental procedure also, using water and R-113 over vertical tube and concluded that the condensation HTC rises 3-3.5%, because of the combined effect of fin crest and trough, as compare to that of Nusselt's prediction [31]. To encounter the surface tension effects, first time the experimental data is presented by Glushchuk [84] for condensation across cylindrical fin under various gravity conditions ranging from normal gravity (go) to low gravity (0.05go).Force balance on the condensate flow is analyzed concerning STPG since STPG has a significant influence in the regions where the condensate film thickness changes dramatically. Fin is divided into seven different regions and heat transfer is observed at each region.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…For this purpose, we used a one-dimensional confocal probe, with which we measured the thickness on several places across the deposition. The optical confocal system for the measurement of the film thickness has been developed in [33]. The thickness is measured locally on three spots where the electrical and thermal conductivities are measured.…”
Section: Thickness Of Deposited Layermentioning
confidence: 99%